Role of the principle of separation of powers in civil proceedings. (Journal of actual problems of jurisprudence, 2016)
This article discusses the impact of the separation of powers in the exercise of civil proceedings. We consider the particular constitutional guarantees of human rights in civil proceedings in the Republic ofKazakhstan.
Keywords: the principle of separation of powers; rule of law; the legislature; the executive; the judiciary